Usability assessment of a greenhouse context-aware alert system for small-scale farmers - Brenes, Jose A.; López, Gustavo; Ferrández-Pastor, Francisco Javier; Marín-Raventós, Gabriela (Frontiers in Computer Science, 2024)
In the dynamic landscape of modern agriculture, integrating technology holds immense potential to enhance efficiency and productivity for small-scale farmers. This study presents a user-centric evaluation of an intelligent context-aware alert system, tailored for small-scale greenhouse farming. Employing standardized questionnaires, including the NASA Task Load Index and the User Experience Questionnaire, we assessed the system's perceived utility, mental workload, and overall user experience. Our findings reveal the high perceived utility of the system among farmers.Farmers participating in the assessment indicate a strong intention to utilize the system for crop monitoring. Moreover, the system demonstrates a moderate mental workload, suggesting ease of use and potential acceptance by users. Our evaluation highlights an excellent user experience, with scores ranging from very good to extremely good across all dimensions. Furthermore, user preferences for alert mechanisms underscore the importance of adaptable notifications, with voice and text alerts favored for comprehensive information dissemination. Light and voice alerts are preferred during manual tasks. This study highlights the significance of user-centered design in agricultural technology, offering insights to enhance the usability and the adoption of alert systems in small-scale farming environments.